HUBUNGAN ANTARA MUTU PELAYANAN DENGAN MINAT MELAKUKAN KUNJUNGAN ULANG ANC DI POLINDES - Fitri Yuniarti (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2016)
The low of ANC repeat-visit is caused by the interestof ANC repeat visits that is low, the interest of ANC repeat visits are influenced by the quality of service, while quality service is determined by the satisfaction of patients, with services that do not match their expectations so the patients not satisfied and the quality of service is low. The objective of this research was to know the correlation between quality of service with an interest to conduct ANC repeat visits in Polindes village of Banyuanyar District of Gurah Kediri regency. The research design used analytic with approach of cross sectional. The collection of data conducted on 2November– 31 December 2013 in Polindes Village of Banyuanyar district of Gurah Kediri regency. The Independent variable was the quality of service and the dependent variable was the interest of ANC repeat visits.Population used pregnant women amount to 53 respondents and sample used technique of probabilitysampling and simple random sampling that was mount to 35 respondents.Instrument of data collection used questionnaire,then analyzed and tested with statistical test of Chi Square, α = 0.05. Based on the test results of Chi Square obtained that x2count> x2 table that was 5.733> 3.841 then Ho rejected and Hi accepted means there wascorrelation between quality of service with interest to conduct ANC repeat-visit. Coefficient of Contingency 0.695 that mean the closeness correlation was strong category. Good quality service means match to the expectations of patient, and then result in satisfaction of patient. The feeling of satisfaction makes the patient have interest to conduct repeat visit of ANC.